Wear pattern of shoes - Chong, Choon Yuan. (2013)
A follow-up study was done to examine in depth the relationships between human walking gait and the wear pattern of shoes worn. With the idea of creating a simple and easy to replicate study on this topic, a walking test, footprint collection and shoe wear experiment was conducted. Using previously designed cart equipment, the walking test was modified for more accurate markings on the volunteers and addition of front footage capture of walking motion for analysis. The Arch Index was introduced to identify the foot type of the footprints collected. A shoe wear experiment is also proposed and conducted on the volunteers for a period of 3 months on 8 volunteers. The results of walking test showed greater consistency and a strong relation between higher ankle rotation and greater lateral heel wear. The results also suggested a difference in both ankle rotation and shoe wear formation between feet, with the master leg gaining dominance in both. Areas of wear specific to foot types were observed and helped explain the degree of pronation involved by different arch types. Other characteristics of human gait such as heel strike and walking gap were examined but found little influences on the shoe wear pattern, suggesting a need for follow-up after a longer period of wear.